To solve the system of equations using elimination, we'll add the two equations together in order to eliminate the variable "x":
(-x - 3y) + (-5x - 3y) = -7 + 25
Simplifying the left side:
-6x - 6y = 18
Divide the entire equation by -6 in order to solve for "y":
(-6x - 6y)/-6 = 18/-6
x + y = -3
Thus, the system of equations simplifies to:
x + y = -3
y = -3 - x
Solve the system of equations using elimination: minus, x, minus, 3, y, equals, minus, 7−x−3y=−7 and minus, 5, x, minus, 3, y, equals, 25−5x−3y=25.
1 answer